Journey Describing the Discoveries of Anti-HIV Triterpene Acid Families Targeting HIV-Entry/Fusion, Protease Functioning and Maturation Stages - V. Patel, Rahul; Won Park, Se (Current Topics in Medicinal Chemistry, 2014)
HIV infection/AIDS, is a fatal disease multiplying rapidly in virtually every country. Extensive creations are in progress to arrest the replication of the HIV, following the destruction of either particular step involved in the progression of HIV infection. In such endeavors, mechanistically more diverse antiviral therapies were showcased using naturally occurring triterpene acid and their derivatives acting at various stages of HIV life cycle like entry or fusion, function of HIV protease enzyme and finally at maturation. The present article holds an extensive step-by-step summary of anti-HIV breakthroughs of triterpene acid analogues and their derivatives with synthetic and activity aspects, featuring fertile clues for novel anti-HIV drug design, which helps to develop unprecedented opportunities to discover the next-generation anti- HIV armamentarium.
Keywords: entry-fusion inhibitors